The United States - O'Donovan, Patrick (New York : Time-Life Books, 1968)
Nine essays illustrated with photographs on various aspects of American civilization and culture, including political history and thought, education, economy, religion, and the Nation's role and influence in the modern world.
Includes bibliographical references and Index.
Keywords: United States -- Civilization -- 1945-; United States -- Civilization